Giant Splenorenal Shunt in a Young Patient with Autoimmune Hepatitis/Primary Biliary Cholangitis Overlap Syndrome and Portal Vein Thrombosis. (20th February 2017) - Chegai, F.; Cavallo, A. U.; Forcina, M.; Giuricin, V.; Castellani, F.; Greco, L.; Manuelli, M.; Manzia, T. M.; Sergiacomi, G.
Abstract : We present a case of giant Splenorenal Shunt (SRS) associated with portal vein thrombosis in a 37-year-old woman with a twelve-year history of autoimmune hepatitis/primary biliary cholangitis overlap syndrome. At the moment of the CT examination laboratory tests showed creatinine 1.5 mg/dl, bilirubin 1.5 mg/dl, INR 3, and Na 145 mmol/l and the Model End-Stage Liver Disease score was 24. Extensive calcified thrombosis causing complete occlusion of the portal vein lumen and partially occluding the origin of the superior mesenteric vein was present and a small calcified thrombus in the Splenic Vein lumen was also evident. SRS was located among the spleen hilum and the left kidney with a maximum diameter of 3.25 cm and was associated with dilatation of left renal vein and inferior vena cava. After a multidisciplinary evaluation the patient was put on the Regional Liver Transplant waiting list and liver transplantation was performed successfully. Although portal vein thrombosis and SRS are common occurrences in cirrhotic patients, the impact in the natural history of the disease is still unclear. Careful management and accurate imaging protocols are essential in the evaluation of those patients.